Frontispiece: Dative Au→Al Interactions: Crystallographic Characterization and Computational Analysis. Issue 1 (2nd January 2015) - Devillard , Marc; Nicolas, Emmanuel; Ehlers, Andreas W.; Backs, Jana; Mallet‐Ladeira, Sonia; Bouhadir , Ghenwa; Slootweg, J. Chris; Uhl, Werner; Bourissou , Didier
<x xml:space="preserve">Abstract</x> Coordination Chemistry The coordination of a geminal phosphorus–aluminum Lewis pair to organo‐gold complexes leads to unprecedented Au→Al interactions, which have been authenticated by X‐ray diffraction and analyzed by DFT calculations. For more details see the Communication by D. Bourissou et al. on page 74 ff.<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>